PTU-063 Bone Protection Therapy in Patients Receiving Glucocorticoid Therapy for Inflammatory Bowel Disease – A Need to Revisit Guidelines?. (17th August 2016) - Everson, M; Sheth, R; Bloom, S
Abstract : Introduction: Patients with inflammatory bowel disease (IBD) have a higher risk of developing reduced bone mineral density (BMD). 1 We aimed to assess our compliance with 2007 BSG guidance 2 on the use of bone protection and DEXA scanning in patients with IBD receiving steroids. Furthermore, we attempted to identify risk factors for the development of low BMD in patients with IBD. Methods: Data was pooled retrospectively on 368 patients with Crohns (CD), ulcerative (UC), indeterminate (IDC) or microscopic (MC) colitis who received steroids as inpatients or outpatients at a tertiary IBD centre from April 2014-October 2015. Patient notes and imaging records were screened to determine if Calcium, Vitamin D supplementation, bone protection therapy and DEXA scans were given in accordance with 2007 BSG guidelines. Data from patients with DEXA-confirmed low BMD (age at diagnosis, sex, disease location, disease duration, vitamin D deficiency) was analysed by logistic regression analysis to determine an association between these characteristics and the development of low BMD. Results: 368 patients (m:190, f: 178, median age 31 yrs [13 – 91 yrs ]) received steroids for IBD (217 CD, 137 UC, 10 IDC, 4 MC ) from Apr 2014 to Oct 2015. Of 314 patients, 145 (46%) received calcium-vitamin D supplementation when indicated. No patients over 65 yrs (n = 27) received bisphosphonate therapy with steroids. DEXA scanning was performed in 62 of 314 eligible patients (16.5%), with 31 (50%) demonstrating low BMD - 18 (29%) osteoporosis, 13 (21%) osteopaenia. 3 patients with low BMD had evidence of fractures, compared with none with normal BMD. Logistic regression analysis showed no statistically significant associations between any of the proposed risk factors and the development of low BMD. Conclusion: As a tertiary centre we demonstrate poor compliance with BSG guidelines for the prevention of low BMD in IBD – we infer that other centres may have even lower compliance. The prevalence of low BMD in this patient group is as high as 50%. Current guidelines on the use of DEXA and bone protection in this subset of patients are vague and lack an evidence base – they suggest that the majority of patients on steroids with IBD undergo DEXA scanning. Larger studies are needed to identify risk factors for low BMD in IBD patients on steroids. The development of more evidence based guidelines would allow these patients to be prioritised for DEXA scanning and bone protective therapies – improving cost efficiency and reducing radiation doses to patients. References: 1 Bjarnason I, Macpherson A, Mackintosh C, et al . Reduced bone density in patients with inflammatory bowel disease. Gut 1997;40 (2):228–233. 2 Guidelines for osteoporosis in inflammatory bowel disease and coeliac disease NR Lewis, BB Scott – BSG guidelines 2007. Disclosure of Interest: None Declared